Let the right one in [videorecording (DVD)] - Alfredson, Tomas, 1965-; Hedebrant, Kåre, 1995-; Leandersson, Lina, 1995-; Ragnar, Per; Ajvide Lindqvist, John, 1968- (Distributed by Magnolia Home Entertainment, 2009)
12-year-old Oscar is a fragile and bullied boy who finds love and revenge when he meets Eli. Eli is a beautiful but peculiar girl he befriends. She has moved into his building. Oscar does not know that she and her father are vampires. When strange disappearances and murders start happening in the town, suspicions mount from her neighbors and police. Eli must move on to stay alive or stay to help Oscar the only way she knows how.